Metal‐Catalyzed Cross‐Coupling Reactions 2004
DOI: 10.1002/9783527619535.ch5
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Coupling of Organyl Halides with Alkenes: the Heck Reaction

Abstract: The carbopalladation of an alkene by an organylpalladium halide is the essential step in one of the major contemporary metal-catalyzed C-C-coupling reactions. About 35 years ago, a Japanese and an American group almost simultaneously designed and executed palladium-mediated coupling reactions of aryl and alkenyl halides with alkenes [1]. In subsequent investigations, Richard Heck and his group developed this reaction into a catalytic transformation and started to demonstrate its usefulness as well as its rathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(35 citation statements)
references
References 751 publications
(306 reference statements)
0
35
0
Order By: Relevance
“…Furthermore, the application of a diazonium salt instead of an arylhalide reduces the amount of salts generated, allowing for a particularly green reaction. This work, one of the few examples of a Pd-catalyzed coupling reaction working on an industrial scale, highlights the power of diazonium chemistry for process chemists. ,, …”
Section: Heck Cross-coupling Reactionsmentioning
confidence: 88%
“…Furthermore, the application of a diazonium salt instead of an arylhalide reduces the amount of salts generated, allowing for a particularly green reaction. This work, one of the few examples of a Pd-catalyzed coupling reaction working on an industrial scale, highlights the power of diazonium chemistry for process chemists. ,, …”
Section: Heck Cross-coupling Reactionsmentioning
confidence: 88%
“…This is illustrated by recent work on OA of aryl-halide bonds to Au(I) complexes, leading to Au(III)(aryl)(halide) complexes, which is a difficult reaction to achieve, compared with the facile OA of aryl-halides to Pd(0). 74 Bickelhaupt showed that the energy barrier for OA of aryl-halides to Au(I) catalysts based on a linear L-Au-L geometry is due to the energy penalty associated with deformation of the linear framework into a bent framework (see Figure 9). 75 At the same time, Au(I) complexes containing chelating diphosphines with small bite angles, thus already deformed towards the bent geometry that they will assume in the oxidative addition transition state/product, perform OA of phenyl iodide to Au(I) at low temperature.…”
Section: The Extension Of Energy Decomposition Analysis To Transitionmentioning
confidence: 99%
“…Typically, alcohols, THF or DMF are used as solvents for Matsuda–Heck reactions. One of the most rapidly developing trends in organic synthesis is the carrying out of reactions in water following a «Green chemistry» approach [ 4 ]. In 2012, examples of the Matsuda–Heck arylation of styrene and acrylic acid esters with arenediazonium tetrafluoroborates in water and catalyzed with in situ formed Pd nanoparticles [ 5 ] or agarose-supported Pd nanoparticles [ 6 ] have been reported.…”
Section: Introductionmentioning
confidence: 99%